Building knowledge in higher education enhancing teaching and learning with legitimation code theory - Winberg, Christine; McKenna, Sioux; Wilmot, Kirstin (Legitmation code theory: knowledge-building in research and practice, 2021)
"Higher education is facing a series of challenges that are redefining the nature of universities. From initiatives to make higher education economically efficient to social justice calls to open the field to a broader range of students, the field of higher education is in a state of flux. Yet studies about higher education teaching and learning, assessment and curricula remain theoretically underdeveloped and segmented by discipline and country. This book illustrates how Legitimation Code Theory is helping to transform the field by bringing research together from across the disciplinary map and by enabling practical change in a rigorously theorised way"--